(untitled) (Revista de Educação Pública, 2012)
O artigo tem o objetivo de situar a obra de Paulo Freire em relação aos movimentos sociais. Argumenta-se que a pedagogia freireana tem nesses movimentos um dos principais lugares de inspiração e de renovação. Na primeira parte há uma tentativa de mapear etapas da obra de Freire e sua vinculação com os movimentos sociais, respectivamente, os movimentos populares dos anos 60 no Brasil; o período do exílio, quando a teoria de Freire é testada no confronto com outras realidades e movimentos; e os movimentos pelos direitos humanos e pela redemocratização após o retorno à sua pátria. Na segunda parte são identificados alguns aspectos do que pode ser caracterizado como pedagogia do movimento: a leitura do mundo desde o interior das práticas sociais, a itinerância ou “andarilhagem”, e a ampliação de fronteiras do “ser mais” a partir dos movimentos sociais como forças instituintes. Pedagogy of movement: Social movements in the work of Paulo Freire Abstract The main purpose of this article is to situate the work of Paulo Freire in relation to social movements. It is argued that Freire’s pedagogy finds in the social movement one of the main loci of inspiration and renewal. In the first part there is an attempt to identify some phases in Freire’s work, and their linkage to social movements, respectively, the popular movements in the decade of 1960 in Brazil; the period of his exile, when Freire’s theory is tested in the confrontation with other realities and movements; and the movements for human rights and for redemocratization after returning to his country. In the second part, there are identified some aspects of what could be characterized as a pedagogy of movement: the reading of the world from within the social practices, the itinerant character of his praxis, and the widening of the meaning of “being more” (ser mais) based on the social movements as creative forces. Keywords: Paulo Freire. Social movements. Popular movements. Popular education. Citizenship.